Harriet's ruffled feathers : the woman who saved millions of birds - McCullough, Joy (Atheneum Books for Young Readers, 2022)
After learning about the millions of birds dying for their feathers, Harriet starts the Massachusetts Audubon Society, dedicated to the conservation and protection of birds. Includes instructions on birdwatching and how to make pretend binoculars.